Mechanical properties and fracture analysis of additively manufactured EH 36 steel parts by laser engineered net shaping process - Jing, Wei (2018)
Metal additive manufacturing (AM) technologies have attracted a lot of interests from many industrial sectors due to its unlimited capability of producing complex geometries. Metal parts with complex shapes at large scales are highly demanded in marine and offshore (M&O) industries. The aim of this paper is to ascertain the feasibility of Additive Manufacturing (to be more specific Laser Engineered Net Shaping) of ASTM A131 EH 36 steel. After doing mechanical testing for LENS processed ASTM A131 EH 36 samples, the LENS processed samples with horizontal build direction have much better mechanical properties comparing with conventionally made parts, however samples with vertical build direction or 45 degree vertical build directions have properties comparable or lower than parts made of conventional methods due to build defects.